The Integrated Islamic Education System in Islamic Movements: A Philosophical Analysis of Wahdah Islamiyah’s Educational Model - Iskandar, Iskandar; Samsuddin, Samsuddin; Idharudin, Abdul Jabar; Maya, Rahendra; Masuwd, Mowafg; Azizah, Balkis Nur (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study examines the integrated Islamic education system developed by the Wahdah Islamiyah Movement as a contemporary model that harmoniously integrates spiritual, intellectual, and social dimensions. The main objective is to provide a philosophical analysis of the ontological, epistemological, and axiological foundations of Wahdah Islamiyah’s educational system in shaping insan kamil (a holistic human being) grounded in tauhid values. Using a qualitative approach with philosophical analysis, this research draws upon official documents, scholarly works of Wahdah Islamiyah’s leaders, and relevant prior studies. The findings indicate that Wahdah Islamiyah’s educational system is integrative, transformative, and rooted in Qur’anic and Prophetic principles. It emphasizes the harmony between knowledge and practice, intellect and spirituality, as well as between formal, non-formal, and informal education. The novelty of this research lies in identifying the philosophical synthesis achieved by Wahdah Islamiyah, which bridges the ideals of classical Islamic education with the demands of modern educational paradigms. This study contributes conceptually to the development of an integrated Islamic education model relevant to contemporary global and societal challenges. Abstrak: Penelitian ini mengkaji sistem pendidikan Islam terpadu yang dikembangkan oleh Gerakan Wahdah Islamiyah sebagai model pendidikan Islam kontemporer yang memadukan dimensi spiritual, intelektual, dan sosial secara seimbang. Tujuan penelitian ini adalah menganalisis secara filosofis landasan ontologis, epistemologis, dan aksiologis sistem pendidikan Wahdah Islamiyah dalam membentuk insan kamil yang berkarakter tauhid. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis filosofis melalui telaah dokumen resmi, karya tokoh-tokoh Wahdah Islamiyah, serta hasil penelitian terdahulu. Hasil analisis menunjukkan bahwa sistem pendidikan Wahdah Islamiyah bersifat integratif, transformatif, dan berlandaskan pada nilai-nilai Al-Qur’an dan As-Sunnah. Model ini menekankan keselarasan antara ilmu dan amal, akal dan hati, serta antara pendidikan formal, non-formal, dan informal. Kebaruan penelitian ini terletak pada temuan bahwa Wahdah Islamiyah berhasil mengintegrasikan idealisme pendidikan Islam klasik dengan kebutuhan pendidikan modern dalam satu kerangka filosofis yang koheren. Temuan ini memberikan kontribusi konseptual terhadap pengembangan model pendidikan Islam terpadu yang relevan dengan tantangan global dan kebutuhan umat.